Landscape gardening on the farm - Marty, Charles Sumner (My University, 1896)
Introduction: In writing on Landscape Gardening, my object is to call the attention of the farmers to an art which in the past, has been much use the present is in its dawn, and promises a bright and glorious day for the future. The art of Landscape Gardening is the designing or an arrangement of buildings, walks, trees, shrubs and flowers that they may be or appear more pleasing and beautiful to man, the art is not only the knowing how, but the doing or carrying out of this work.
Citation: Marty, Charles Sumner. Landscape gardening on the farm. Senior thesis, Kansas State Agricultural College, 1896.
Morse Department of Special Collections
Keywords: Landscape gardening; Farmers; Flowers; Shrubs; Theses; Manuscripts (documents)